Applications of artificial atom algorithm to small-scale traveling salesman problems - Yildirim, Ayse Erdogan; Karci, Ali (Springer, 2018)
Most of the meta-heuristic algorithms are based on the natural processes. They were inspired by physical, biological, social, chemical, social-biological, biological-geography, music, and hybrid processes. In this paper, artificial atom algorithm which was inspired by one of natural processes was applied to traveling salesman problem. The obtained results have shown that for small-scale TSP, artificial atom algorithm is closer to optimum than the other compared heuristic algorithms such as tabu search, genetic algorithm, particle swarm optimization, ant colony optimization, and their different combinations.
Keywords: Meta-heuristic approaches; Traveling salesman problem; Artificial atom algorithm; Genetic algorithm; Particle swarm optimization; Ant colony optimization